Actualidad de la neurosis de angustia (2008)
ABSTRACT: The anguish neurosis, as a concept and clinical nosological category, is strictly Freudian, and was born in the field of psychoanalysis. It surges in opposition to the concept of psychoneurosis, and for that reason, their symptoms are not interpretable and to that extent, they are not affordable by psychoanalysis. But despite that, the anguish neurosis retains all its value, while its symptoms are particular applications of libido and require a revision of this notion in light of new psychoanalytical research. It also contributes to an understanding of the formation of symptoms in hysteria and obsession, as a reflection on the relationship of sexuality with the real. The problem of the anguish and the two theories of Freud on this: as a result of repression and as a result, warrants a reflection on this paradox. Lacan refers to the real anguish, to define it as its sole subjective translation and therefore, as an affection that does not fool, and can tackle it from the logical consistency of the object, while retaining the Freudian perspective in which the anguish is not interpretable, and if it is not interpretable, we have to pass through in the analysis.